Stakeholders’ interaction in emerging Tourism Awareness Group as a community-based tourism management - Peni Arianita Wardani; Muhamad Farhan; Nur Afni Rachman; Meiga Rahmanita; Damianus Sonny Lamoren (School of Tourism, Universitas Ciputra Surabaya, 2026)
The emergence of a new tourism destination typically requires the creation of an institutional framework to regulate, manage, and ensure the long-term sustainability of the area. However, establishing such institutions can be complex. In this context, the institutionalization process is influenced by dynamic interactions among diverse stakeholders, which can significantly affect the success or failure of the new institution. This study examines stakeholder interactions in forming a Tourism Awareness Group, which serves as a mechanism for community-based tourism management in Kelor Tourism Village. The research particularly underscores the strategic efforts of initiators to Influence and engage various stakeholders throughout the institutionalization process. This descriptive qualitative study, utilizing a discursive institutionalism framework, analyses how ideas and discourses serve as crucial instruments in the emergence of innovative institutions. Ten informants were selected based on their involvement in the Tourism Awareness Group. The findings indicate that the initiators proposed key concepts, including economic development through tourism, community-based tourism governance, establishing a Tourism Awareness Group, and incentives for community participation, initially developed through coordinative discourse with influential local actors. These concepts were subsequently disseminated to the broader community via communicative discourse. The success of Kelor Tourism Village was further bolstered by the initiators' ability to communicate effectively, negotiate competing interests, and mobilize social and human capital. This study presents a theoretical contribution to tourism village management from an institutional perspective. In addition, this research provides valuable empirical insights into similar tourism destinations, facilitating the optimization of community-based management practices.